A Panoramic View System of Guilin Tourism Based on Interactive Projection Technology. (June 2020) - Yu, Ke; Shi, Zhuo; Feng, Ye; Shen, Tianlong; Huang, Zhixiong; Gu, Yinwei; Deng, Yingzhuo; Liang, Yushi
Abstract: This paper introduces a panoramic view system of Guilin Tourism based on virtual reality and infrared image tracking. Users interact with images on the ground through body movements, the system can achieve unattended, interactive guided, automatic voice interpretation function, with virtualization, high efficiency, easy maintenance, good interactive experience and so on. Suitable for placing in exhibition venues, scenic spots exhibition hall and so on, so that tourists can enjoy Guilin landscape without leaving home.